Caracterização de germoplasma e sazonalidade em erva-cidreira-brasileira [Lippia alba (Mill.) N. E. Br.] - Camêlo, Lídia Cristina Alves (2010)
Lippia alba (Mill.) N. E. Br. is a medicinal plant widely distributed and used in Brazil, because of its sedative activity of the essential oil. This study aimed to characterize and evaluate the behavior of accessions of Lippia alba (Mill.) N. E. Br., collected in several states of Brazil, and maintained in the Active Germplasm Bank of the Federal University of Sergipe (UFS), São Cristóvão county. The first chapter presented a general introduction of the work, the theoretical study about the relationship between genetic resources, seasonality and sustainability in Agroecosystems, origin, botanical aspects and use of L. alba, the essential oil and morphological, agronomic and chemical characterization of germplasm. The second chapter consisted of morphological and agronomic characterization of L. alba germplasm grown in field, using a randomized block design with two replications. The evaluated variables were: length of branch, crown diameter, growth habit, length, width and length/width ratio of leaf, color of stems, veins, leaves, sepals and petals, dry weight of leaves, essential oil content and yield. The results showed morphological differences among accessions for the following variables: length of branch, crown diameter, color of stems, leaves and petals, growth habit, length, width and length/width ratio of leaves. Differences were observed for essential oil content and yield, and the accession LA-60 presented best results for essential oil yield. In the third chapter the chemical composition of the L. alba accessions of the Active Germplasm Bank of the UFS. The chemical composition of essential oils distinguished the accessions into six groups and we observed that Group 3 is formed only by the accession LA-13, which presented predominantly limonene and carvone. In the fourth chapter, the seasonal variation in L. alba genotypes were studied, harvesting in four different seasons. The best results were obtained in the first harvest, which was realized at the end of the rainy season (September/2008). The plants showed higher chemical constituents content at the third harvest (March/2009).